PAD Model Effects on Tourists’ Attitudes and Intention Pengaruh Reaksi Afektif Terhadap Sikap dan Dampaknya Pada Niat Kunjungan Wisatawan - Andy Mulyana; Ida ayu Made Er Meytha Gayatri; Tri Febrina Melinda (UNIVED Press, 2022)
This study aims to find out and analyze the influence of affective reactions of tourists on attitudes and their impact on tourist visit intentions. Therefore, this research approach is in accordance with its purpose using a descriptive research and verificative research approach. The research method or technique used in this study is a survey, which is a field research conducted on several sample members of a certain population to find out the perception of some of the population towards the object of study so that actual data or information is obtained. The data collected is in the form of primary data with research instruments in the form of questionnaires. with a total of 93 respondents. Statistical tests and data processing were carried out using Partial Least Square (SmartPLS 3.0). On the relationship of Arousal with Pleasure, the value of t counting the arousal variable is 9.925. Because the calculated t value is greater than 1.96, Ha is accepted meaning that Arousal has a significant influence with a positive direction on Pleasure. On the relationship of Attitude to Intention, the value of t counting the variable Attitude is 7.215. Because the calculated t value is greater than 1.96, Ha is accepted, meaning that Attitude has a significant influence with a positive direction on Intention. On the relationship of Dominance with Arousal, the value of t counting the dominance variable is 14,700. Because the calculated t value is greater than 1.96, Ha is accepted meaning that Dominance exerts a significant influence in a positive direction towards Arousal. On Dominance's relationship with Pleasure, The calculated t value of the Dominance variable is 5,086. Because the calculated t value is greater than 1.96, Ha is accepted meaning that Dominance exerts a significant influence in a positive direction on Pleasure. On the relationship of Pleasure to Attitude, the value of t counting the variable Pleasure is 7.301. Because the calculated t value is greater than 1.96, Ha is accepted, meaning that Pleasure has a significant influence with a positive direction on Attitude. For R square pleasure, it has a greater influence compared to other variables with a value of 0.645 or 64.5%.